2020
DOI: 10.1111/arcm.12631
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the formation and diagnostic value of ω‐(o‐alkylphenyl)alkanoic acids in ancient pottery

Abstract: Long-chain ω-(o-alkylphenyl)alkanoic acids (APAAs) derived from the heating of unsaturated fatty acids have been widely used for the identification of aquatic products in archaeological ceramic vessels. To date, little attention has been paid to the diagnostic potential of shorter chain (< C 20 ) APAAs, despite their frequent occurrence. Here, a range of laboratory and field experiments and analyses of archaeological samples were undertaken to investigate whether APAAs could be used to further differentiate di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…The ratio of the two isomers of phytanic acid varied from 45 to 76% of SSR diastereoisomer. Markers of thermal transformation of animal fats (Bondetti et al, 2020;Hansel et al, 2004;Raven et al, 1997) were also detected occasionally. Traces of ω-(oalkylphenyl)alkanoic acids (APAAs) with 18 carbon atoms were detected in 3 samples (AP_0008, AP_0027, and AP_0036; Figure 4) but no C20-APAAS.…”
Section: Resultsmentioning
confidence: 96%
“…The ratio of the two isomers of phytanic acid varied from 45 to 76% of SSR diastereoisomer. Markers of thermal transformation of animal fats (Bondetti et al, 2020;Hansel et al, 2004;Raven et al, 1997) were also detected occasionally. Traces of ω-(oalkylphenyl)alkanoic acids (APAAs) with 18 carbon atoms were detected in 3 samples (AP_0008, AP_0027, and AP_0036; Figure 4) but no C20-APAAS.…”
Section: Resultsmentioning
confidence: 96%
“…A similar set of plant biomarkers has been identified in Bronze Age pottery vessels from the Korean Peninsula and northern Europe and reported as the first molecular and isotopic evidence of millet processing in prehistoric pottery vessels [ 57 ]. Another class of compounds identified in all ten acidified methanol extracts are isomers of the ω-(o-alkylphenyl) alkanoic acid (AAPA) with 18 carbon atoms, which are readily formed by heating a wide range of resources rich in unsaturated fatty acids precursors (C 18:x ), notably plant and aquatic resources, but also a number of terrestrial products [ 58 60 ]. While previous studies had shown that APAAs were formed when vessels are subjected to temperatures exceeding 270°C for at least 17 hours [ 58 ], recent experimental work has shown that these compounds are formed over just one hour of heating at 270°C, or at 200°C for 5 hours, conditions easily achieved through both boiling or roasting [ 60 , 61 ].…”
Section: Molecular and Isotopic Characterization Of Ten Ma’an Jarsmentioning
confidence: 99%
“…Another class of compounds identified in all ten acidified methanol extracts are isomers of the ω-(o-alkylphenyl) alkanoic acid (AAPA) with 18 carbon atoms, which are readily formed by heating a wide range of resources rich in unsaturated fatty acids precursors (C 18:x ), notably plant and aquatic resources, but also a number of terrestrial products [ 58 60 ]. While previous studies had shown that APAAs were formed when vessels are subjected to temperatures exceeding 270°C for at least 17 hours [ 58 ], recent experimental work has shown that these compounds are formed over just one hour of heating at 270°C, or at 200°C for 5 hours, conditions easily achieved through both boiling or roasting [ 60 , 61 ]. Similar experiments also show that the relative abundance of certain APAA-C 18 isomers (namely the E and H isomers—see Fig 11 ) can effectively separate three groups of food products: 1) cereals/fruits/non-leafy vegetables, 2) leafy vegetables, and 3) animal/aquatic products [ 60 ].…”
Section: Molecular and Isotopic Characterization Of Ten Ma’an Jarsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, being close to the (actual) see level, this set of ceramics has an added complexity of strong marine influences, reflected by for instance mollusks growing on potsherd surfaces. In addition, such coastal environments may be more likely to contain residues of aquatic resources that produce isoprenoid fatty acids [25][26][27].…”
Section: Introductionmentioning
confidence: 99%